2017
DOI: 10.1002/pts.2339
|View full text |Cite
|
Sign up to set email alerts
|

Influence of side stripe on the corrosion of unlacquered tinplate cans for food preserves

Abstract: Metal containers are used for packaging foodstuffs; more specifically, the cans used for preserving fruit have a plain body with side seam protected by a lacquer film. The traditionally used side stripe is adopted “out of abundance of caution”, as the tin present on the seam is removed by the welding process. Not using a side stripe would have practical/functional benefits for the entire production chain, with consequent reduction in the cost of the containers and in their environmental impact. Packaging of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Tinplate finds its main application in containers for packaging [1]. The manufacturing process of these cans includes a cylindrical body produced by forming rectangular blanks around a mandrel and soldering (now increasingly rare), resistance welding, or occasionally cementing the side seam [2][3][4][5]. Soldering changes the state of the tin coating and welding modifies the steel near the weld.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tinplate finds its main application in containers for packaging [1]. The manufacturing process of these cans includes a cylindrical body produced by forming rectangular blanks around a mandrel and soldering (now increasingly rare), resistance welding, or occasionally cementing the side seam [2][3][4][5]. Soldering changes the state of the tin coating and welding modifies the steel near the weld.…”
Section: Introductionmentioning
confidence: 99%
“…Soldering changes the state of the tin coating and welding modifies the steel near the weld. Both welding and cementing can produce lap joints that may have exposed edges and the possibility of crevices [3]. Moreover, the tinplate surface may undergo major deformation with disruption of the tin coating.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These coatings are applied as an internal organic lining over the base metal in order to provide an inert barrier between the metal and the food product. 6 Because of its excellent toughness, corrosion resistivity and high adhesive properties to metals, epoxy resin became a perfect material to coat food cans. 7 Huang et al 8 reported that in 2011, 5.5 million tons of BPA were produced, making it one of the world's most abundantly produced industrial chemical at that time.…”
mentioning
confidence: 99%